Core Cross‐Linked Polymeric Micelles for Specific Iron Delivery: Inducing Sterile Inflammation in Macrophages. Issue 19 (16th June 2021) - Bauer, Tobias A.; Horvat, Natalie K.; Marques, Oriana; Chocarro, Sara; Mertens, Christina; Colucci, Silvia; Schmitt, Sascha; Carrella, Luca M.; Morsbach, Svenja; Koynov, Kaloian; Fenaroli, Federico; Blümler, Peter; et al.
Abstract: Iron is an essential co‐factor for cellular processes. In the immune system, it can activate macrophages and represents a potential therapeutic for various diseases. To specifically deliver iron to macrophages, iron oxide nanoparticles are embedded in polymeric micelles of reactive polysarcosine ‐block‐ poly( S ‐ethylsulfonyl‐l ‐cysteine). Upon surface functionalization via dihydrolipoic acid, iron oxide cores act as crosslinker themselves and undergo chemoselective disulfide bond formation with the surrounding poly( S ‐ethylsulfonyl‐l ‐cysteine) block, yielding glutathione‐responsive core cross‐linked polymeric micelles (CCPMs). When applied to primary murine and human macrophages, these nanoparticles display preferential uptake, sustained intracellular iron release, and induce a strong inflammatory response. This response is also demonstrated in vivo when nanoparticles are intratracheally administered to wild‐type C57Bl/6N mice. Most importantly, the controlled release concept to deliver iron oxide in redox‐responsive CCPMs induces significantly stronger macrophage activation than any other iron source at identical iron levels (e.g., Feraheme), directing to a new class of immune therapeutics. Abstract : Delivery of iron to macrophages triggers sterile inflammation. To provide stable encapsulation in human blood plasma yet triggered release inside cells, superparamagnetic iron oxide nanoparticles (SPIONs) are surface‐functionalized and embedded in core cross‐linked micelles derived of polypept(o)ides. Stimulated uptake and degradation by macrophages induce strong inflammatory responses establishing SPION‐core cross‐linked polymeric micelles an immunostimulatory agent to counteract undesired immune tolerance.